Exciton and Charge Carrier Dynamics in Highly Crystalline PTQ10:IDIC Organic Solar Cells - Harrison Lee (Advanced Energy Materials, 2020)
Herein the morphology and exciton/charge carrier dynamics in bulk heterojunctions (BHJs) of the donor polymer PTQ10 and molecular acceptor IDIC are investigated. PTQ10:IDIC BHJs are shown to be particularly promising for low cost organic solar cells (OSCs). It is found that both PTQ10 and IDIC show remarkably high crystallinity in optimized BHJs, with GIWAXS data indicating pi‐pi stacking coherence lengths of up to 8 nm. Exciton‐exciton annihilation studies indicate long exciton diffusion lengths for both neat materials (19 nm for PTQ10 and 9.5 nm for IDIC), enabling efficient exciton separation with half lives of 1 and 3 ps, despite the high degree of phase segregation in this blend. Transient absorption data indicate exciton separation leads to the formation of two spectrally distinct species, assigned to interfacial charge transfer (CT) states and separated charges. CT state decay is correlated with the appearance of additional separate charges, indicating relatively efficient CT state dissociation, attributed to the high crystallinity of this blend. The results emphasize the potential for high material crystallinity to enhance charge separation and collection in OSCs, but also that long exciton diffusion lengths are likely to be essential for efficient exciton separation in such high crystallinity devices.